Development and validation of instruments to assess content knowledge and topic specific pedagogical content knowledge of teachers of organic chemistry - Vokwana, Nonkanyiso Queen (Department of Chemistry, 2014)
In 1986, Shulman described Pedagogical Content Knowledge (PCK), as the transformation of Content Knowledge into various forms which help students to understand the concepts. In a later study, Shulman (1987) identified the construct of PCK as one of the knowledge bases of teachers. Many researchers have proposed models to characterise this transformation of Content Knowledge (CK), one of the most recent of which describes the construct of Topic Specific PCK (TSPCK) (Mavhunga, 2012). This study attempts to evaluate the extent to which teachers of organic chemistry are able to transform their CK to TSPCK. The introduction of the National Curriculum Statement in South Africa in 2006 led to changes in the curriculum for all subjects; in particular there was an increase in emphasis on organic chemistry at Grade 12 level. The current research forms part of a larger project to investigate how teachers' knowledge of their subject matter affects the way they teach across several different contexts. It is premised on the assumption that PCK develops with experience and results from the transformation of CK. Two instruments based on the Mavhunga (2012) model were designed to assess Grade 12 teachers' TSPCK in organic chemistry. Her model proposes that topic specific PCK results from the transformation of CK; thus Content Knowledge is considered to be a prerequisite to develop TSPCK. Thus two instruments are required, one each to evaluate CK and TSPCK. A pilot study was conducted with a small group of teachers and the findings were used to refine the instruments. Expert teachers at local schools were consulted and assisted in the development process of the instruments, the final versions of which were administered to a larger cohort of 44 science teachers from diverse schools. The CK instrument was assessed as a conventional test on organic chemistry while the TSPCK instrument was scored using a specially designed rubric. The research methodology used a mixed methods approach to transform data collected into numerical clusters as well as to carry out a qualitative analysis. The data was analysed to yield raw scores which were later subjected to Rasch analysis. This measurement model was used to validate the instruments and also to convert raw scores into interval data. According to the Rasch analysis, both instruments met the criteria of validity and internal consistency. The findings from the CK instrument revealed that the majority of teachers performed well. Teachers with university training achieved higher scores than those trained at technikons and colleges. Performance on the TSPCK instrument was not as strong as for CK; teachers with little experience revealed less complete levels of TSPCK than those with more experience. A reasonable correlation between levels of CK and TSPCK was confirmed by a value of r = 0.68 (p< .0005) for the correlation coefficient derived from a scatter plot of CK versus TSPCK. This implies that an estimated 46% of the variance in TSPCK is accounted for by the variance in CK and provides evidence for the assumption that CK is a prerequisite for TSPCK. The main findings from this project revealed that low levels of CK are likely to result in lower levels of TSPCK while high levels of CK are likely to result in high levels of TSPCK. On the other hand the study also revealed that high levels of CK do not necessarily translate into high levels of TSPCK. An unanticipated outcome of the study was that in some cases, lower than average levels of CK can translate into high levels of TSPCK. The Rasch analysis also enabled the refinement of the CK instrument and the rubric developed to score the TSPCK instrument. The refinements will allow the researchers to use the valuable data collected during the course of this particular study as part of a data set for any future study. The instruments developed for this study have the potential to be used for a large-scale implementation to obtain a more nuanced picture of the level of PCK in organic chemistry in the teaching cohort in South Africa.